Phenotype of matrin‐3–related distal myopathy in 16 German patients. Issue 5 (16th September 2014) - Müller, Tobias J.; Kraya, Torsten; Stoltenburg‐Didinger, Gisela; Hanisch, Frank; Kornhuber, Malte; Stoevesandt, Dietrich; Senderek, Jan; Weis, Joachim; Baum, Petra; Deschauer, Marcus; Zierz, Stephan
<x xml:space="preserve">Abstract</x> Objective To characterize the phenotype of patients with distal myopathy with vocal cord and pharyngeal weakness due to the p.S85C mutation in the matrin‐3 gene (MATR3, Mendelian Inheritance in Man 164015). Recently, it has been suggested that patients with this mutation may suffer from familial amyotrophic lateral sclerosis. Methods Sixteen patients from 6 families with late onset distal myopathy associated with the p.S85C MATR3 mutation were characterized. Results Patients had a predominantly distal muscle weakness, most severely affecting ankle and wrist dorsiflexion. Relevant proximal and axial weakness was found in 6 and respiratory impairment in 5 patients. Dysphagia was diagnosed in 6 and mild voice abnormalities were found in 7 patients. However, laryngoscopy revealed normal vocal cord function. Creatine kinase was normal or mildly elevated. Electromyographically, spontaneous activity was found in 10 of 14 patients and complex repetitive discharges in 9 of 14 patients. Magnetic resonance imaging revealed severe fatty degeneration of distal and upper posterior leg and of paraspinal muscles. Histopathology ranged from mild myopathic to severe dystrophic changes including vacuoles. Absence of sarcomeres in the perinuclear region and abnormal invaginations of nuclei were found ultrastructurally. Haplotype analysis showed a common disease‐specific haplotype of the 6 families and suggested that these families form a separate cluster. Interpretation In contrast to the 2 previously reported families, MATR3‐related distal myopathy might be associated with relevant axial, proximal, and respiratory muscle weakness but without vocal cord palsy. There were no clinical, electrophysiological, or histopathological signs of lower motor neuron involvement. Ann Neurol 2014;76:669–680